Konseling Individual dengan Teknik Motivational Interviewing untuk Menangani Penyesuaian Sosial pada Remaja Tindak Pidana Pencurian di Yayasan Sahabat Kapas Karanganyar - Nareswari, Swastika Rizki; Khairi, Alfin Miftahul; Nafi’, Ahmad (IAIN Kudus, 2020)
Individual Counseling with Motivational Interviewing Techniques to Deal with Social Adjustments in Adolescent Criminal Theft in Yayasan Sahabat Kapas Karanganyar. This study aims to determine the process of individual counseling services with Motivational Interviewing Techniques to deal with social adjustment in adolescent criminal acts of theft at the Sahabat Kapas Karanganyar Foundation. The research method uses descriptive qualitative methods. Data collection techniques using interviews, observation, and documentation. The results showed that individual counseling with Motivational Interviewing Techniques would be maximized by implementing four principles to deal with social adjustmentKeywords: Individual Counseling, Motivational Interviewing, Social Adjustment